Septin/anillin filaments scaffold central nervous system myelin to accelerate nerve conduction - Julia Patzig; Michelle S Erwig; Stefan Tenzer; Kathrin Kusch; Payam Dibaj; Wiebke Möbius; Sandra Goebbels; Nicole Schaeren-Wiemers; Klaus-Armin Nave; Hauke B Werner (eLife, 2016)
Myelination of axons facilitates rapid impulse propagation in the nervous system. The axon/myelin-unit becomes impaired in myelin-related disorders and upon normal aging. However, the molecular cause of many pathological features, including the frequently observed myelin outfoldings, remained unknown. Using label-free quantitative proteomics, we find that the presence of myelin outfoldings correlates with a loss of cytoskeletal septins in myelin. Regulated by phosphatidylinositol-(4,5)-bisphosphate (PI(4,5)P2)-levels, myelin septins (SEPT2/SEPT4/SEPT7/SEPT8) and the PI(4,5)P2-adaptor anillin form previously unrecognized filaments that extend longitudinally along myelinated axons. By confocal microscopy and immunogold-electron microscopy, these filaments are localized to the non-compacted adaxonal myelin compartment. Genetic disruption of these filaments in Sept8-mutant mice causes myelin outfoldings as a very specific neuropathology. Septin filaments thus serve an important function in scaffolding the axon/myelin-unit, evidently a late stage of myelin maturation. We propose that pathological or aging-associated diminishment of the septin/anillin-scaffold causes myelin outfoldings that impair the normal nerve conduction velocity.